Etiology of patients with extreme thrombocytosis and its association with coagulation function: 10-year experience in a tertiary hospital - Chen, Huadong; Huang, Shuying; Wu, Gongqiang; Zhang, Zhenjiao; Yu, Zhenwei; Chen, Qiaoyun; Ying, Manzhen (Frontiers in Medicine, 2025)
BackgroundIdentifying the cause of extreme thrombocytosis is important, but few data exist. This study aimed to analyze the etiology of extreme thrombocytosis and its influence on coagulation function.MethodsWe performed a ten-year retrospective study that included patients with platelet counts >1,000 × 109/L. The etiology of extreme thrombocytosis was analyzed by physicians and compared between subgroups, which were stratified by department, age and sex. We also collected the coagulation function of inpatients, including the prothrombin time (PT), international normalized ratio, partial thromboplastin time ratio, prothrombin activity, activated partial thromboplastin time (APTT), fibrinogen, thrombin time and D-dimer, when patients were under extreme thrombocytosis.ResultsOverall, 437 patients were included in the study, including 254 inpatients, 125 outpatients, and 58 emergency patients. The most common cause was myeloproliferative neoplasms (MPN), followed by infection and asplenia. However, the etiology of disease in nearly 10% (41/437) of patients is unclear. MPN was the main etiology for patients from different departments, but the second most common etiologies for inpatients, outpatients and emergency patients were infection, chronic myelogenous leukemia, and unknown, respectively. The most common cause in children is infection. There was no difference between females and males, except for asplenia. Among the inpatients, 87.5 and 60.1% of the patients had PT and D-dimer higher than the normal range, respectively. Moreover, APTT and FIB were in critical condition for 11.1 and 13.7% of the patients, respectively.ConclusionThis study provides the etiology of extreme thrombocytosis and its association with coagulation function. This study could benefit the future diagnosis and treatment of extreme thrombocytosis.